Blood Group A and B Determinants Are Expressed on Platelet Glycoproteins IIa, IIIa, and Ib - Santoso, S; Kiefel, V; Mueller-Eckhardt, C (Thrombosis and Haemostasis, 1991)
We report the localization of A, B blood group determinants on intrinsic glycoproteins using anti-A, B IgG antibodies. By radioimmunoprecipitation, anti-A and anti-B precipitated three bands with apparent molecular masses in sodium dodecylsulphate- polyacrylamide gel electrophoresis (SDS-PAGE) of 159, ~ 120 and 85 kDa under non-reduced conditions and 145, ~ 126 and 97 kDa under reduced conditions. In two-dimensional gel electrophoresis (isoelectric focussing/SDS-PAGE) these three bands could be resolved into six spots and fulfilled previously defined citeria for platelet membrane glycoprotein complexes Ia/IIa, Ic’IIIa, Ib/IX and IIb/IIIa. The results were supported by data obtained by an assay employing antibody-specific immobilizatisn of platelet antigens (MAIPA). By this technique, blood group A, B determinants were shown to be immobilized by monoclonal antibodies specific for GPIa, Ic’, IX, IIb/IIIa and strongly by mab specific for GPIIa, but not by mab specific for HLA class I molecules.The more precise localization on platelet glycoproteins was achieved by immunoblotting technique by which blood group A determinants could be assigned to GPs IIa, IIIa and Ib.